PENGHAYATAN IMAN KATOLIK DI TENGAH MASYARAKAT METROPOLITAN ERA DAN PASCA PANDEMI COVID-19 - Dadi, Kanisius Komsiah (CREDENDUM: Jurnal Pendidikan Agama, 2022)
Spread Covid-19 local, national, and global scales, have yet to finish. The Covid-19 pandemic has impacted many aspects of human social life significantly. This study aims to describe the impact of the Covid-19 pandemic on metropolitan Christians' faith expression and how they keep their Christian character in this situation. Based on Salvifici Doloris Ensiclic, Pope John Paul II instructed Christians to have true faith and a new mindset. When Christians are in famines and pestilences, run into earthquakes in various places, or are snared in war, or a pandemic situation, in that case, they should be more focused on God's direction, and His Will and have a deep relationship with Him. The message of John Paul II, in Salvifici Doloris Ensiclic, is clear that Christians need to have true hope, love, and strong faith. Saint Luke (The Gospel of Luke chapter 21) tough that Christ's disciples need to have seven characters. These characters are the face of the early Church to now Church. To support this study, the researcher designed and did online field research using google Forms as a research instrument or tool for getting data. The research subjects are Jakarta Dioces Christians as metropolitan people. The researcher used quantitative data (percentage) and descriptive analysis techniques. So, the researcher changes quantitative data to become qualitative. The result of this research is that the Covid-19 pandemic significantly impacted the faith expression of metropolitan Christians. The pandemic impacted the way Christians treated others and expressed their faith. This pandemic built Christian values and characters of metropolitan Christians to become better than before. Metropolitan Christians are braver in helping others. They are more responsible toward others who are hungry and suffering. They are more expressive in faith, more open and loving each other, more robust in faith, and more settled in God's word. They have more creative thinking in creating the solution.